Yield To Maturity Corporate Bonds: Indonesian Capital Market - Abdul Latif; Erna Apriani (Cita Konsultindo Research Center, 2022)
In 2021, the Indonesian economy was in the recovery phase after the COVID-19 pandemic, which is felt by almost all stakeholders in investment instruments, especially in corporate bond transactions, the issuance of which has increased from the previous year, which means that issuers and investors are starting to get busy so that it becomes an effective form of the recovery phase. From the publisher, investor, and national side. From this background, the researcher aims to analyze how much and how much influence 1). Profitability to yield to maturity. 2). leverage on yield to maturity. 3). Company size on yield to maturity. 4). Bond rating on yield to maturity. The method in this study belongs to the type of causality with a quantitative application, the population in this study is non-bank corporate bonds and financial institutions that are still traded in 2021, with a sample of 230 corporate bonds from 47 issuing companies; the analysis technique used is multiple linear regression with SPSS 25 analysis tool. The results of this study explain that the variable return on assets, debt-to-equity ratio, and firm size do not affect the yield to maturity of bonds. Still, in contrast to the bond rating variable, it can influence in a positive direction the yield to maturity of bonds.